Reliability and responsiveness of the Uchi-Komi fitness test among judo athletes - Souissi, N.; Chaabène, H.; Trabelsi, K.; Romdhani, M.; Chtourou, H.; Clark, C. C. (South African Journal for Research in Sport, Physical Education and Recreation, 2024)
Several tests have been designed to assess the ability of judoka to repeat specific and intense efforts of short duration. To be accepted and adopted, the reliability and construct validity of the test should be confirmed. This study aimed to examine the relative and absolute reliability and the external responsiveness of an intermittent test simulating judo combat (the Uchi-Komi Fitness Test). Seventeen judo athletes of two different levels of performance (elite and non-elite), performed the Uchi-Komi Fitness Test during three sessions separated by 72 hours. The number of Uchi-Komi was recorded. In addition, blood lactate concentration and rating of perceived exertion were measured. The Uchi-Komi Fitness Test showed good relative and absolute reliability in detecting small and meaningful changes. The performances were better in elite vs. non-elite counterparts (p=0.006). Receiver operating characteristic analysis showed that the Uchi-Komi Fitness Test was able to discriminate athletes of different competitive level (receiver operating characteristic curve 0.83). The Uchi-Komi Fitness Test is a good indicator of physical fitness specific to judo and can discriminate between elite and non-elite judokas.